Urban Shrinkage, Degrowth, and Sustainability: An Updated Research Agenda - de Kraker, Joop (2024)
Shrinking cities and degrowth thinking share their parting from the dominant growth paradigm and seem to have much to offer to each other. Could degrowth be an inspiring and guiding paradigm for the sustainable development of shrinking cities? Could shrinking cities be suitable testing grounds to apply degrowth’s radical sustainability principles in practice? These and other questions regarding the connections between urban shrinkage, degrowth, and sustainability have hardly been addressed in the scientific literature thus far. This thematic issue brings together novel empirical contributions, taking stock of first attempts to connect degrowth to urban shrinkage, exploring in how far this potential unfolds in practice and what obstacles these attempts face, with a focus on the field of urban planning. In this editorial, we discuss the connections between shrinking cities, degrowth, and sustainability identified in the empirical studies and the dialogues that span across these contributions. We conclude with an updated research agenda for this field of study.